THE DICHOTOMY BETWEEN HEAT SHOCK PROTEIN-27 AND MICROALBUMIN: COVARIATE OF EARLY DIABETIC NEPHROPATHY - Muhammad Irfan; Fatima Abid; Azhar, Arfa; Farooqui, Mohammad Umair; Urooj Fatima; Siddiqui, Muhammad Subhan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Heat shock protein-27 is the microprotein released from renal parenchyma during diabetic oxidative stress, while microalbumin is the plasma protein that appears in urine in diabetic nephropathy. Methods: This case-control study was conducted from Jan to Sep 2021 in the Physiology department, BMC, BMCH, Quetta. The current study included 105 patients with an age range from 30-50 years and was divided into three groups: i) a control group of healthy participants, ii) a diabetic risk group: participants without signs of diabetic nephropathy and diabetic duration from 1-5 years, iii) diabetic nephropathy group: participants having >30 mg/dl of v microalbumin in urine and diabetic duration from 5-10 years. Results: There were significant mean differences between all groups with respect to anthropometric measurements except in height amongst all groups. Statistically significant mean differences were seen in the risk and nephropathy group with respect to serum FBG, RBG, and HbA1c. Elevated microalbumin levels in the diabetic nephropathy group (50.9±8.2) compared with the diabetic risk group (15.4±2.9). Similarly, higher levels of HSP-27 were seen in the diabetic nephropathy group (230.46±23.75) as compared with the diabetic risk group (117.60±14.50). Conclusion: HSP-27 is a better biomarker than microalbumin and may show early glomerular injury in the early diabetic stage of diabetic nephropathy